Shariah non-compliance treatment in Malaysian Islamic Banks - Hani Nabila binti Omar (IIUM Institute of Banking and Finance, International Islamic University Malaysia, 2019)
Islamic finance in Malaysia has been growing rapidly in the past 30 years and continues to thrive in many countries. In 2019, a total of 16 Islamic banks (IBs) is listed and supervised by Bank Negara Malaysia (BNM) with 5 banks being foreign entities. In view of the rivalry with the conventional banking sector, Islamic banks (IBs) offer new innovative Islamic products and financial projects which may lead to greater risk of Shariah non-compliance (SNC) exposure to the Islamic Financial Institutions (IFIs) in its effort to stay competitive. This study attempts to explore IBs current practice of treating the SNC and the extent of compliance with BNM rules and guidelines focusing on the BNM Operational Risk Integrated Online Network (ORION) requirement on SNC reporting event. This study also intends to review the challenges faced by IBs and propose recommendations for the existing policy to enhance the treatment of SNC. This study adopts qualitative research method by conducting semi-structured in-depth interviews with Islamic banking professionals targeting five IBs. Both the primary and secondary sources are used for data collection. The finding shows that IBs adhere to the BNM rules and requirements, with some minor differences in the implementation process. The finding of this study would contribute positively in terms of establishing the level of compliance of the banks as well as facilitating policy makers and regulators on enhancing the regulations and practices in ensuring zero SNC events. Simultaneously, the existing literature on the SNC practices by IBs will be expanded so that more researchers can have larger resource of reference to diversify the topics related to this study. Key words: Shariah non-compliance, risk, Shariah non-compliance event, Shariah non-compliance reporting, Islamic banks, BNM guidelines